2003
DOI: 10.1364/oe.11.001430
|View full text |Cite
|
Sign up to set email alerts
|

Self-starting optoelectronic oscillator for generating ultra-low-jitter high-rate (10GHz or higher) optical pulses

Abstract: We demonstrate a novel, self-starting optoelectronic oscillator based on an electro-absorption modulator in a fiber-extended cavity for generating an optical pulse stream with high-rate and ultra-low jitter capabilities. Optical pulses at 10GHz repetition rate are demonstrated with >90dBc/Hz side-mode suppression and the lowest timing jitter (42fs in the 100Hz-1MHz range) reported to date for a self-starting source. Along with the optical pulse stream, the oscillator also generates a 10GHz electrical signal wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…An EOO typically incorporates a nonlinear (intensity) modulator, an optical-fibre delay line, and an optical detector in a closed-loop resonating configuration. This hybrid microwave source is capable of generating, within the same optoelectronic cavity, either an ultra-low-jitter (low phase-noise) single-tone microwave oscillation, as used in radar applications [25][26][27], or a broadband chaotic carrier typically intended for physical data encryption in high bit rate optical communications [28]. For a specific range of values of the parameters, periodic square-wave oscillations (figure 2) were found exhibiting a period P close to one delay t D as well as different plateau lengths.…”
Section: Introductionmentioning
confidence: 99%
“…An EOO typically incorporates a nonlinear (intensity) modulator, an optical-fibre delay line, and an optical detector in a closed-loop resonating configuration. This hybrid microwave source is capable of generating, within the same optoelectronic cavity, either an ultra-low-jitter (low phase-noise) single-tone microwave oscillation, as used in radar applications [25][26][27], or a broadband chaotic carrier typically intended for physical data encryption in high bit rate optical communications [28]. For a specific range of values of the parameters, periodic square-wave oscillations (figure 2) were found exhibiting a period P close to one delay t D as well as different plateau lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Note that there is a limit to the improvement of the phase noise as the length of fiber increases. As shown by Lasri et al [21], the improvement in the timing jitter, derived from the phase noise as shown in (1), of an OEO has an inverse square root dependence on the fiber length. The limitations are due to the random fiber length variations due to small fluctuations in the environment around the fiber span.…”
Section: Basic Operation Of the Oeomentioning
confidence: 88%
“…Unfortunately as the fiber length increases, the spacing between the cavity modes decreases. For example, a 3 km length of fiber will yield a cavity mode spacing of approximately 67 kHz [21]. A high quality electrical bandpass filter at 10 GHz has a 3 dB bandwidth of 10 MHz [22].…”
Section: Multi-loop Oeomentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the relative simplicity of the mathematical model and the good quantitative agreement with experiments, an OEO is a particularly desirable set up if we wish to explore delay-induced instabilities in the laboratory [36]. These instabilities and their control have led to new applications for secure optical communication [37], radars requiring ultra-pure sources of light [38][39][40], and neuromorphic computing [41,42].…”
Section: Introductionmentioning
confidence: 99%